Keeper of the lost cities - Messenger, Shannon (Messenger, Shannon. Keeper of the lost cities, 2012)
At age twelve, Sophie learns that the remarkable abilities that have always caused her to stand out identify her as an elf, and after being brought to Eternalia to hone her skills, discovers that she has secrets buried in her memory for which some would kill.